Gastritis May Boost Odds of Dementia. (August 2014) - Momtaz, Yadollah Abolfathi; Hamid, Tengku Aizan; Ibrahim, Rahimah
Introduction: Given the high prevalence of dementia and its devastating consequences, identifying risk factors for dementia is a public health priority. The present study aims to assess whether gastritis increases the odds of dementia. Methodology: The data for this study, consisting of 2926 community-dwelling older adults, were obtained from the National survey entitled "Mental Health and Quality of Life of Older Malaysians." Dementia was diagnosed using the Geriatric Mental State-Automated Geriatric Examination for Computer-Assisted Taxonomy. Results: Prevalence of dementia was considerably higher among older adults with gastritis (29.5%) compared to those without gastritis (13.2%). After adjusting for age, gender, marital status, educational attainment, hypertension, stroke, and diabetes, gastritis was significantly associated with more than twice odds of dementia (adjusted odds ratio = 2.42, P < .001, 95% confidence interval = 1.68-3.49). Conclusions: The findings from this population-based observational study showing evidence that gastritis may increase the risk of dementia provide avenue for further inquiries into dementia.